Sabtu Penuh Kehangatan: Pemeriksaan Kesehatan dan Manisnya Berbagi Bubur Kacang Hijau untuk Lansia di Posyandu Lansia Cendrawasih RT. 09 Kelurahan Karang Anyar Pantai - Nurul Hidayat; Abi Dermawan; Siti Nadiah; Dwi Rahmawati; Muhammad Chaidir; Yashar Arifandya Ramadhan; Muhammad Rizaldi; Elsa Mayorah (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
The global increase in life expectancy has significantly contributed to the growth of the elderly population, including in Indonesia, which has now entered the aging population phase with more than 10% of its total population aged 60 years and above. This demographic shift presents challenges in maintaining the quality of life among the elderly, particularly in tropical border regions such as Tarakan City. Karang Anyar Pantai Village, located in West Tarakan District, has a considerable number of elderly residents supported by existing elderly health posts (posyandu lansia). Social and health interventions through elderly exercise programs, nutritional support in the form of mung bean porridge, and regular monthly health check-ups are considered strategic efforts to improve physical health, metabolic function, and psychological well-being among the elderly. This study aims to evaluate the impact of these three interventions on enhancing the quality of life of the elderly in Karang Anyar Pantai. By assessing the effectiveness of these interventions, this research seeks to provide recommendations for improving elderly care programs in similar regions.